Physicochemical and nutritional properties of taro (Colocasia esculenta L. Schott) flour as affected by drying temperature and air velocity - Arici, Muhammet; Yildirim, Rusen Metin; Ozulku, Gorkem; Yasar, Burcu; Toker, Omer Said (ELSEVIER, 2016)
The effect of drying temperature and air velocity on the chemical composition, colour, parameters, total and resistant starch contents, bioactive and pasting properties of the taro flours were investigated in the present study. For this aim, taro tubers were dried at different temperature (40, 50 and 60 degrees C) and air velocity (0.75, 1.25 and 2.00 m/s) levels. Generally all characteristics of the flours were significantly affected by drying conditions. Resistant starch of the flours changed between 33.1 g and 51.4 g/100 g flour and the flour produced at 50 degrees C and 2.00 m/s had the highest resistant starch content. Total phenolic content of the flours varied between 1.20 and 4.17 g GAEL and it generally increased with increasing air velocity. Pasting properties of the starches were also markedly influenced and the flour manufactured at 50 degrees C with 0.50 m/s air velocity showed the lowest retrogradation and syneresis rate considering setback values. Final viscosity of the taro flours ranged between 2219 and 3085 cP. The results of the present study indicated that drying temperature and air velocity should be adjusted regarding physicochemical properties of the taro flours, determining probable usage areas of the flours. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Taro flour; Pasting properties; Bioactive properties; Resistant starch; Drying; COCOYAM XANTHOSOMA-SAGITTIFOLIUM; ANTIOXIDANT ACTIVITY; CHEMICAL-COMPOSITION; DIGESTIBILITY; Food Science & Technology